SOCIAL CULTURE AND PUBLIC PARTICIPATION IN THE DEVELOPMENT OF KAMPUNG KOTA: A CASE STUDY IN BANDUNG INDONESIA - Ana Ramdani Sari (Lembaga Penelitian Universitas Pasundan, 2021)
Kampung Kota has been associated with slums due to its substandard living condition despite having different characteristics to slums. To improve the quality of life of Kampung Kota community; it is important to actively involve the community itself to transform Kampung Kota to better direction and to exercise the democracy within urban development. The research aims to understand in what ways the community has been involved, how the community perceived their involvement, how the community wish to be involved and in what ways community participation could be improved in transforming Mekarjaya and maximizing its social capital. The research was conducted using qualitative methodology and case study strategy. Interviews, observation and documentary evidences are used to collect the data and to validate the date by cross-checking every information using triangulation technique. The research finds that the community has not been actively involved in many programs and projects due to the nature of the government programs that support the funding. However, most of the people; whose voice are generally represented by the head of RT/RW (Community unit/neighbourhood unit); are far more eager and willingly contribute to the development if they have the platform to do so.